Antibody response to booster doses of hepatitis b vaccine in medical students vaccinated in infancy - Mohd Noh, Dr Rosnida; Abd Jalil, Afdhal; Ibrahim, Azlina; Sahlan, Noraziah (Research and Innovation Division, Universiti Teknologi MARA (UiTM) Selangor, 2025)
(This study investigates the antibody response to booster doses of the hepatitis B vaccine in medical students vaccinated during infancy. Hepatitis B vaccination has been part of Malaysia's National Immunisation Programme since 1989, with no routine post-vaccination antibody measurements. This study aimed to evaluate antibody levels and the response to booster doses in individuals who completed the primary vaccination series in infancy but no longer had protective antibody levels (anti-HBs <10 mIU/ml). A descriptive prospective study was conducted on medical students from Universiti Teknologi MARA. Participants with written proof of completing the three-dose primary series were included. Antibody levels were measured at baseline, seven days after the first booster dose, 28 days after the second dose, six months after the third dose, and one-month post-final booster. The recombinant hepatitis B vaccine Euvax B, containing 20 µg of hepatitis B surface antigen with an aluminium hydroxide adjuvant, was used. Anti-HBs levels were measured using an electrochemiluminescent immunoassay (COBAS E411 analyser). Of 152 participants, 19.08% had baseline protective antibody levels (≥10 mIU/ml). Fifty-six students with evidence of prior vaccination were eligible for the study, and 37 completed the full protocol. At seven days post-first dose, 8/37 (21.62%) achieved protective antibody levels, rising to 31/37 (83.78%) by 28 days and 37/37 (100%) by six months. The findings indicated a robust anamnestic response in most participants, with a single booster dose restoring protective antibody levels in 83.78%. The study highlights the waning of hepatitis B antibodies 19–20 years post-primary immunisation. Although protective levels persisted in 19% of young adults, most participants responded to a single booster dose, reaffirming the effectiveness of the vaccination program. The results support booster vaccination for healthcare workers to ensure adequate protection against hepatitis B.